Norming the Norm of Relationality: A Theological and Interreligious Exploration of the Trinitarian Doctrine - David Muthukumar Sivasubramanian (Jurnal Jaffray, 2020)
Should all metaphysical reflections on the Trinity begin with the “substance/essence” ontology? This approach has frequently regression into metaphysical speculation, as in the historical theology of the Church. Are there alternative models that we can glean from the history of the Church that can provide a new means of conceptualizing the doctrine of the Trinity? This essay considers this issue at length to suggest a “relational ontology” paradigm in constructing the Trinitarian doctrine. It also makes use of Vishishtadvaita (Qualified Non-Dualism in Hindu philosophy) conception of “body-soul” analogy to render a “qualitative panentheistic” model in construing the doctrine of the Trinity. These theological and interreligious explorations are expected to shed more light on the issue.Haruskah semua refleksi metafisik tentang Trinitas bermula dengan ontologi “substansi/esensi”? Pendekatan ini seringkali menyebabkan kemunduran spekulasi metafisik, sebagaimana disaksikan dalam teologi sejarah gereja. Apakah ada model alternatif yang bisa kita ambil dari sejarah gereja yang dapat menyediakan cara baru untuk mengkonsepkan doktrin Trinitas? Esai ini mempertimbangkan isu ini panjang lebar untuk menunjukkan paradigma “ontologi relasional” dalam membina doktrin Trinitarian. Hal ini juga membuat penggunaan Vishishtadvaita (Kualifikasi Non-Dualisme dalam filsafat Hindu) konsepsi analogi “tubuh-jiwa” untuk membuat model “kualitatif panenteistik” dalam membangun doktrin Trinitas. Eksplorasi teologi dan keberagaman agama ini diharapkan lebih menjelaskan masalah ini.